Changing Principal Leadership in the Age of Digitalization - Irawan, David Budi; Marisya, Fitria; Hatidah, Hatidah; Purwanto, Muhammad Bambang (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The purpose of this research is to investigate how student learning results, teacher professional development, and the efficacy of school administration are affected by the shift in leadership in the digital age in technology-driven management of education governance. A qualitative research approach was used in the study's design, and semi-structured interviews with teachers, students, and school administrators were used to collect data. Triangulation method was used in the research to analyse school policy documents and practices pertaining to technology integration. At SD Muhammadiyah 14 Palembang, the results demonstrated a considerable improvement in students' academic performance through technology-based education management. Personalized learning materials are made available to students through the use of educational software and online resources, which also improves academic performance. Furthermore, the use of digital platforms for feedback and evaluation has made it easier for teachers to monitor students' progress in real time and effectively, enabling them to offer focused interventions. The present study underscores the noteworthy influence of technology-driven education governance on the academic achievements of students, the professional growth of educators, and the efficiency of school administration at SD Muhammadiyah 14 Palembang. The study points up a number of integration-related difficulties that school administrators must carefully analyse and handle. The study's recommendations are intended to address these issues and enhance the efficacy of SD Muhammadiyah 14 Palembang's technology-based education management in the digital age.